Poverty Reduction Policies and Practices in Developing Asia - Heshmati, Almas; Maasoumi, Esfandiar; Wan, Guanghua (Economic Studies in Inequality, Social Exclusion and Well-Being, 2015)
Development Economics; Economic Policy; Social Policy; Climate Change Management and Policy